Keragaman dan Produktivitas Hijauan Pakan Indigenous pada Berbagai Tingkat Kerapatan Vegetasi di Pegunungan Kapur Gombong Selatan - Doso Sarwanto; Sari Eko Tuswati; Pudji Widodo (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
Research aims to conduct diversity and productivity of indigenous forage in different levels vegetation density in Gombong-Selatan karst mountain. We used survey method to explain the research by sampled three location of vegetation density, they are moderate, high, and very high. In each location vegetation density we take five parts by using random sampling. Then, a descriptive technique is used to analyzed the indigenous forage diversity data result whereas variance analysis is used to analyzed the productivity.The results shows the highest diversity of indigenous forage in Gombong-Selatan karst mountain is in moderate vegetation density area where has 36 species, high vegetation density has 20 species, and the highest vegetation density has 16 species. Eragrotis amabillis, Oplismenus burmannii, Centrosema pubescens, Ageratum conyzoides and Urena lobata are the dominant indegenous forage species in Gombong-Selatan karst mountain. The variances result shows that indigenous forage productivity in Gombong Selatan karst mountain is influenced by vegetation density. We found that lowest productivity is in high vegetation density.